The Role of CT Imaging in Characterization of Small Renal Masses - Maria Vittoria Bazzocchi; Carlotta Zilioli; Vita Ida Gallone; Claudia Commisso; Lorenzo Bertolotti; Francesco Pagnini; Francesco Ziglioli; Umberto Maestroni; Alberto Aliprandi; Sebastiano Buti; Giuseppe Procopio; Giorgio Ascenti; et al. (Diagnostics, 2023)
Small renal masses (SRM) are increasingly detected incidentally during imaging. They vary widely in histology and aggressiveness, and include benign renal tumors and renal cell carcinomas that can be either indolent or aggressive. Imaging plays a key role in the characterization of these small renal masses. While a confident diagnosis can be made in many cases, some renal masses are indeterminate at imaging and can present as diagnostic dilemmas for both the radiologists and the referring clinicians. This review focuses on CT characterization of small renal masses, perhaps helping us understand small renal masses. The following aspects were considered for the review: (a) assessing the presence of fat, (b) assessing the enhancement, (c) differentiating renal tumor subtype, and (d) identifying valuable CT signs.